The role of physical controllers in motion video gaming - Freeman, Dustin; Hilliges, Otmar; Sellen, Abigail; O'Hara, Kenton; Izadi, Shahram (Proceedings of Designing Interactive Systems (DIS), 2012)
Systems that detect the unaugmented human body allow players to interact without using a physical controller. But how is interaction altered by the absence of a physical input device? What is the impact on game performance, on a player’s expectation of their ability to control the game, and on their game experience? In this study, we investigate these issues in the context of a table tennis video game. The results show that the impact of holding a physical controller, or indeed of the fidelity of that controller, does not appear in simple measures of performance. Rather, the difference between controllers is a function of the responsiveness of the game being controlled, as well as other factors to do with expectations, real world game experience and social context.